Military and Civilian: Reconfiguring the End of Roman Britain in the North. (1st May 2013) - Petts, David
<x xml:space="preserve">Abstract</x> This study explores the impact of recent discoveries on our understanding of the transition from the Roman to early medieval periods in northern England. Using the Tees Valley as a case study, it shows how modern interpretations of this process have focused primarily on the afterlife of the military sites in the region. However, the increased identification of significant Roman civilian settlements forces us to reconsider the dominant narratives and rethink the underlying processes that influenced the move from Roman-controlled frontier society in the fourth century to a fifth century society comprising both culturally Anglo-Saxon social groups and sub-Roman successor polities. A wider consideration is also given to how the changing patterns in the use of space and in refuse disposal strategies can be used to shed light on wider patterns of changing social identity in the later fourth century AD.